2021
DOI: 10.18037/ausbd.1039499
|View full text |Cite
|
Sign up to set email alerts
|

Postmodern Culture and Public Relations: An Analysis through Campaigns

Abstract: Despite the diversity of paradigms in the field of public relations, it is evident that the dominant paradigm in the field is the functional paradigm, which defines public relations as a "management function". It leads to the ignorance of "cultural function" of public relations and becomes an obstacle to the development of the field. By establishing a relationship between public relations and culture, this article addresses public relations as a "cultural intermediary" profession that is influenced by the post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…[4, p. 64] suggested that public relations is "the active participation in social construction of meaning". In addition, [6] proposed the 'sociocultural approach' as an alternative paradigm in the field, in which public relations would both affect and be affected by culture, thus, it is viewed as a profession that alters the structure of society through producing, maintaining and organising cultural meanings. Albeit with the emergence of various definitions in defining the public relations profession as a whole, the modern definition by the Public Relations Society of America which defines public relations as "a strategic communication process that builds mutually beneficial relationships between organisations and their publics" remains its relevance [7, para.…”
Section: Public Relations (And Its Definitions)mentioning
confidence: 99%
“…[4, p. 64] suggested that public relations is "the active participation in social construction of meaning". In addition, [6] proposed the 'sociocultural approach' as an alternative paradigm in the field, in which public relations would both affect and be affected by culture, thus, it is viewed as a profession that alters the structure of society through producing, maintaining and organising cultural meanings. Albeit with the emergence of various definitions in defining the public relations profession as a whole, the modern definition by the Public Relations Society of America which defines public relations as "a strategic communication process that builds mutually beneficial relationships between organisations and their publics" remains its relevance [7, para.…”
Section: Public Relations (And Its Definitions)mentioning
confidence: 99%